Pemahaman Hadis Doa Pengalihan Hujan Pendekatan Geografis Jakarta menurut Ali Mustafa Yaqub - Fatihunnada Anis; Afaf Nazrat Uyun (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2020)
This article will explain and analyze Ali Mustafa Yaqub’s hadith understanding on the hadith of transferring a heavy rain with a geographical approach. The author observes that there are still many problems of misunderstanding on this type of hadith that are apparent among Indonesian Muslim communities, especially the citizen of Jakarta when facing heavy rains and floods in early 2020. The geography science is not a source of Islamic law, but this science can be one of the instruments on understanding the hadith correctly. Based on the geomorphology of geography, the hadith prayer for transferring a heavy rain cannot be practiced by the Jakarta residents because that prayer will only cause floods in Jakarta due to heavy rain that came down in Bogor and return to Jakarta. Ali Mustafa offered a prayer for the citizens of Jakarta when facing heavy rain with the phrase